2017
DOI: 10.1111/1365-2656.12670
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night alters trophic interactions of intertidal invertebrates

Abstract: Despite being globally widespread in coastal regions, the impacts of light pollution on intertidal ecosystems has received little attention. Intertidal species exhibit many night-time-dependent ecological strategies, including feeding, reproduction, orientation and predator avoidance, which are likely negatively affected by shifting light regimes, as has been observed in terrestrial and aquatic taxa. Coastal lighting may shape intertidal communities through its influence on the nocturnal foraging activity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 62 publications
4
49
0
1
Order By: Relevance
“…Knowledge of biological and ecological effects of ALAN is rapidly growing, but impacts on marine coastal ecosystems are still underexplored. Recent studies revealed effects on predator− prey interactions including invertebrates and fish, due to influences on their behavior (Bolton et al 2017, Underwood et al 2017. Here, we report the first evidence of alteration in herbivore−resource relationships in marine assemblages, due to direct and indirect effects of ALAN .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Knowledge of biological and ecological effects of ALAN is rapidly growing, but impacts on marine coastal ecosystems are still underexplored. Recent studies revealed effects on predator− prey interactions including invertebrates and fish, due to influences on their behavior (Bolton et al 2017, Underwood et al 2017. Here, we report the first evidence of alteration in herbivore−resource relationships in marine assemblages, due to direct and indirect effects of ALAN .…”
Section: Discussionsupporting
confidence: 55%
“…By disrupting natural light/dark cycles, ALAN is expected to influence primary producers either directly (through photosynthetic activity and cell growth; see Jacquet et al 2001) or indirectly through its effect on grazing pressure. Here, we provide an experimental test of these hypotheses by manipulating nighttime artificial lighting and gastropod grazers in a rocky intertidal food web, where microphytobenthos (MPB) covering rock surfaces represents the main fraction of biomass produced and a key food resource for grazers (Underwood et al 2017).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Artificial lights increased prey intake by several species of wading shorebirds, which could result in longer term depletion of local invertebrate densities (Santos et al, 2010). Similarly, artificial lighting influenced the foraging behavior of the dogwhelk (Nucella lapillus), a predatory mollusk, with potential cascading effects on the community structure of intertidal fauna (Underwood, Davies, & Queir os, 2017). Artificial light had a varied effect on prey consumption by a community of insectivorous bat species, whereby several bat species showed an increased consumption of their preferred prey type (Cravens, Brown, Divoll, & Boyles, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because ALAN is linked closely to human activity (Elvidge et al, ), it is assumed to affect freshwater systems and coastal areas disproportionally (Zhao, Li, Li, Zhao, & Wu, ). The effects of ALAN on aquatic organisms and communities have been researched in several laboratory (Brüning, Hölker, Franke, Kleiner, & Kloas, ; Brüning, Hölker, Franke, Preuer, & Kloas, ; Hölker et al, ; Kurvers et al, ; Perkin, Hölker, Heller, & Berghahn, ; Poulin et al, ; Szekeres et al, ) and field studies (Becker, Whitfield, Cowley, Järnegren, & Næsje, ; Bolton et al, ; Brüning, Kloas, Preuer, & Hölker, ; Cullen & McCarthy, ; Davies, Duffy, Bennie, & Gaston, ; Grubisic et al, ; Grubisic, van Grunsven, Manfrin, Monaghan, & Hölker, ; Hölker et al, ; Ludvigsen et al, ; Manfrin et al, , ; Meyer & Sullivan, ; Moore, Pierce, Walsh, Kvalvik, & Lim, ; Perkin, Hölker, & Tockner, ; Perkin, Hölker, Tockner, & Richardson, ; Riley, Bendall, Ives, Edmonds, & Maxwell, ; Riley, Davison, Maxwell, & Bendall, ; Szaz et al, ; Tabor, Brown, & Luiting, ; Underwood, Davies, & Queirós, ). However, we found a knowledge gap regarding the status quo of light pollution in and along aquatic systems.…”
Section: Introductionmentioning
confidence: 99%